RUBER: Recoverable UAV-based energy-efficient reconfigurable routing scheme for smart wireless livestock sensor network - Alanezi, Mohammed A.; Salami, Abdulazeez F.; Sha’aban, Yusuf A.; Bouchekara, Houssem R. E. H. (Frontiers in Energy Research, 2022)
This paper is a sequel to a previous article by the authors in which UAV-based energy-efficient reconfigurable routing (UBER) scheme was proposed to address coverage loss and rapid energy depletion issues for for smart wireless livestock sensor networks. Sensor node and route failure issues associated with the UBER scheme are therefore addressed in this research by proposing a recoverable UAV-based energy-efficient reconfigurable routing (RUBER) scheme. RUBER scheme relies on an efficient fault detection and recycling technique, dynamic recovery mechanism, and robust route maintenance technique. Performance of RUBER was analyzed under low, medium and high failure rate network conditions. Performance indices employed for this assessment are failure detection ratio (FDR), failure recovery ratio (FRR), load balancing ratio (LBR), and packet delivery ratio (PDR). Analysis results demonstrated that keeping the failure rate below 10% led to performance improvements of 60.96%, 74.14%, 64.68%, and 60.74% for FDR, FRR, LBR, and PDR, respectively. Performance comparison of RUBER was conducted against UBER and hybrid heterogeneous routing (HYBRID) schemes. Performance metrics utilized for this comparative evaluation are average routing delay (ARD), energy dissipation ratio (EDR), routing overhead (ROH), fault tolerance index (FTI), nodal failure recovered (NFR), route failure recovered (RFR), and cluster survival ratio (CSR). With respect to best-case values, RUBER exhibited gains of 79.67%, 44.98%, 67.88%, 74.90%, 52.20%, 70.56%, and 52.52% over UBER and HYBRID in terms of ARD, EDR, ROH, FTI, NFR, RFR, and CSR respectively. Simulation experiments revealed the relative competitiveness of the RUBER scheme against the benchmarked schemes.